Conservation and Diversity of Hempedu Bumi (Andrographis Paniculata Nees) Germplasm in Malaysia - Addisu Biffa, Melaku (2003)
Andrographis paniculata, a member of Accantaceae family, is a soft wooded herbaceous plant having multiple uses in traditional as well as pharmacological (modern) medicine. Collection was carried out on A. paniculat a germplasm from Selangor, Negeri Sembilan and Perak states of Peninsular Malaysia. The objectives of the study were to conserve A. paniculata germplasm from different agroecological conditions of Peninsular Malaysia, to analyze variability and rationalize the germplasm accessions using agro-morphological traits and to evaluate the germ plasm and thereby identify promising genotypes. As noticed during the collection activity, the habitat preference of the plant was wide. The ranges of habitats include neglected fields invaded with noxious weeds, rocky and poor soil conditions and backyard of houses in villages. Of the total 38 accessions collected, 26 were evaluated in the field using Randomized Complete Block Design in three replications. The coefficient of variation values for most of the quantitative morphological characters were generally moderate. Moreover, the qualitative traits such as mature and immature leaf color, leaf shape, plant growth habit and stem color showed the presence of d ifferent types within the germplasm studied. Cluster analYSis done on 26 accessions showed the presence of four d istinct groups. However, this grouping pattern did not show parallelism between the geographical and genetic diversity. The result generally showed the existence of similar genotypes in all of the three states considered u nder this study. Principal component analysis showed the first two axes represent 66.67% of the total variation that identified the importance of flowering date, shoot fresh weight, root fresh weight, leaf dry weight, stem dry weight, root dry weight and root volume towards genetic divergence. The first axis was able to differentiate the first two groups from the 3rd and 4th groups from the cluster analysis. Heritability values revealed high to moderate for flowering date, shoot fresh weight, root dry weight, root fresh weight, branch length, root volume, plant height, leaf dry weight and leaf width.